The tetrahedral phosphoranyl radicals - Evans J.C.; Mishra S.P. (My University, 2025)
Various ESR studies on a variety of phosphoranyl radicals with at least two halide ligands have shown that such radicals have trigonal bipyramidal structures in which the unpaired electron occupies one equatorial site. However, certain mono-halo phosphoranyl radicals show a tetrahedral configuration wherein the odd electron is accommodated in the phosphorus-halogen σ* bond. © 1981.